Identification of a rectal subregion highly predictive of rectal bleeding in prostate cancer IMRT. Issue 3 (June 2016) - Dréan, Gaël; Acosta, Oscar; Ospina, Juan D.; Fargeas, Auréline; Lafond, Caroline; Corrégé, Gwenaelle; Lagrange, Jean-L.; Créhange, Gilles; Simon, Antoine; Haigron, Pascal; de Crevoisier, Renaud
Abstract: Background and purpose: To identify rectal subregions at risks (SRR) highly predictive of 3-year rectal bleeding (RB) in prostate cancer IMRT. Materials and methods: Overall, 173 prostate cancer patients treated with IMRT/IGRT were prospectively analyzed, divided into "training" ( n = 118) and "validation" cohorts ( n = 53). Dose–volume histograms (DVHs) were calculated in three types of rectal subregions: "geometric", intuitively defined (hemi-rectum, …); "personalized", obtained by non-rigid registration followed by voxel-wise statistical analysis (SRRp); "generic", mapped from SRRps, located within 8 × 8 rectal subsections (SRRg). DVHs from patients with and without RB were compared and used for toxicity prediction. Results: Training cohort SRRps were primarily within the inferior anterior hemi-rectum and upper anal canal, with 3.8 Gy mean dose increase for Grade ⩾ 1 RB patients. The SRRg, representing 15% of the absolute rectal volume, was located in 10 inferior–anterior rectal subsections. V18–V70 for SRRps and V58–V65 for SRRg were significantly higher for RB patients than non-RB. Maximum areas under the curve (AUCs) for SRRp and SRRg RB prediction were 71% and 64%, respectively. The validation cohort confirmed the predictive value of SRRg for Grade ⩾ 1 RB. The total cohort confirmed the predictive value of SRRg for Grade ⩾ 2 RB. Geometrical subregions were not RB predictors. Conclusion: The inferior–anterior hemi anorectum was highly predictive of RB.